An Integrative Christian Bioethical Framework: Case Analysis of Pothoven and Lambert - Ratih Runtu , Kezia; Butarbutar , Ferdinandus (Theological Journal Kerugma, 2025)
Death is an inevitable fact of life, and euthanasia is often an option to end suffering. This study seeks to explore Christian ethical considerations of euthanasia through the case studies of Noa Pothoven, a depressive teenager, and Vincent Lambert, a quadriplegic patient. The need for this research arises from the growing public debate about euthanasia and its significance to reaffirming the Christian ethical perspective on the issue. The methodology used is a qualitative analysis of the Pothoven and Lambert cases, with a biblical and theological basis to understand euthanasia from the perspective of the Christian faith. The purpose of this research is to examine euthanasia through the lens of the sanctity of life, the sovereignty of God, and the value of suffering, including providing ethical enlightenment for Christians in dealing with the complexity of this problem. The results of the research show that the Christian perspective rejects active and involuntary euthanasia because it violates the sixth commandment (you shall not kill) and ignores the sanctity of life. However, natural passive euthanasia is acceptable in irreversible conditions after maximum medical efforts. Finally, the findings of this research also encourage an ethical awareness of praxis to preserve life and provide spiritual and emotional support for those who suffer and survive.